Research note: Inverse propagation in 1.5‐dimensional amplitude‐versus‐offset joint migration inversion. (29th September 2021) - Sun, Yimin; Verschuur, Eric
ABSTRACT: The state‐of‐the‐art joint migration inversion faces the so‐called amplitude‐versus‐offset challenge, due to adopting over‐simplified one‐way propagation, reflection and transmission operators to avoid over‐parameterization in the inversion process. To overcome this challenge, we apply joint migration inversion to horizontally layered media (or 1.5‐dimensional media) and parameterize the solution space via density and velocity models. In this scenario, one‐way propagation, reflection and transmission operators required by the joint migration inversion process can be analytically and correctly derived from the subsurface models, so the amplitude‐versus‐offset challenge is successfully overcome. We introduce a new concept, which is named 'inverse propagation', into our 1.5‐dimensional amplitude‐versus‐offset joint migration inversion. It can correctly reconstruct subsurface wavefields by using a surface‐recorded receiver wavefield with all the influence of transmission, reflection and multiples accounted for. A synthetic example is used to demonstrate the correctness of the inverse propagation. This work is the foundation to further develop the 1.5‐dimensional amplitude‐versus‐offset joint migration inversion technology.